Sleep–wake regulation and the hallmarks of the pathogenesis of Alzheimer's disease. Issue 4 (14th January 2019) - Van Egroo, Maxime; Narbutas, Justinas; Chylinski, Daphne; Villar González, Pamela; Maquet, Pierre; Salmon, Eric; Bastin, Christine; Collette, Fabienne; Vandewalle, Gilles
Abstract: While efficient treatments for Alzheimer's disease (AD) remain elusive, a growing body of research has highlighted sleep–wake regulation as a potential modifiable factor to delay disease progression. Evidence accumulated in recent years is pointing toward a tight link between sleep–wake disruption and the three main hallmarks of the pathogenesis of AD, i.e. abnormal amyloid-beta (Aβ) and tau proteins accumulation, and neurodegeneration. However, all three hallmarks are rarely considered together in the same study. In this review, we gather and discuss findings in favor of an association between sleep–wake disruption and each AD hallmark in animal models and in humans, with a focus on the preclinical stages of the disease. We emphasize that these relationships are likely bidirectional for each of these hallmarks. Altogether, current findings provide strong support for considering sleep–wake disruption as a true risk factor in the early unfolding of AD, but more research integrating recent technical advances is needed, particularly with respect to tau protein and neurodegeneration. Interventional longitudinal studies among cognitively healthy older individuals should assess the practical use of improving sleep–wake regulation to slow down the progression of AD pathogenesis.